TECHNICAL STUDY ON THE COMPARATIVE PLANNING OF A WASTE COLLECTION VESSEL PROPULSION SYSTEM: CONVENTIONAL ENGINE AND SOLAR PANELS - Ariani, Betty; Robby, Burhana (Department of Marine Engineering, Universitas Hang Tuah, 2024)
Conventional diesel engines, also known as mechanical direct injection systems, represent a traditional approach to fuel delivery in engines. In contrast, solar panels convert sunlight into electrical energy using the photovoltaic effect. This research aims to conduct a technical comparative study on the planning of a waste collection vessel propulsion system using both conventional diesel engines and solar panels. The vessel system design requires 3.78 hp. The battery capacity calculated for this system is 84.24 Ah, with an operational duration of 6.4 hours for the diesel engine. The waste capacity is 0.371 m³/ton, with a power requirement of 3.75 hp, and the chosen engine for this setup is the Yamaha 5CHMS. For the solar panel system, the potential calculation is 5.47 hours of sunlight, with a similar vessel system design of 3.78 hp. The battery usage duration is 6 hours, with the same waste capacity and power requirement. The selected solar panel is the Hangkai DNYSJYSJ. Based on technical calculations, it can be concluded that a waste collection vessel with a conventional diesel engine is more efficient due to its consistent technical performance requirements.